THE MEANING OF ‘AN‘ANAH AMONG TRANSMISSION TERMS: A Historical Review Based on Primary Ḥadīth Sources from the 2nd to the 6th Century AH - Ali Ziad Nazar (Nabawi: Journal of Hadith Studies, 2024)
In the early centuries of Islam, transmission terms like ḥaddathanī and anbaʾanī were replaced by ʿanʿana to simplify book production and reduce costs. While this facilitated knowledge dissemination, it also raised concerns about the reliability of isnād. This study examines the validity of ʿanʿana-based hadith and its impact on riwāya and fiqh. It explores whether ʿanʿana ensures an unbroken chain of transmission or allows for possible disconnection. Using a critical historical analysis of riwāya literature from the 2nd to 6th centuries AH, this study identifies four scholarly positions: (1) Imam Muslim—accepts mere contemporaneity without tadlīs, (2) Imam Bukhari—requires direct meetings, (3) a stricter view—demands explicit auditory transmission (samāʿ), and (4) a more lenient approach—requires only prolonged companionship. The study challenges the dominance of Imam Bukhari’s position in early Islamic history and highlights ambiguity in the term ʿan. It concludes that while ʿanʿana does not definitively indicate samāʿ, its reliability as a transmission method remains uncertain. These findings have significant implications for the acceptance of ʿanʿana-based hadith and its application in Islamic scholarship.